TEACHERS’ AND SCHOOL HEADS’ POSITION ABOUT THE CHANGES AND PROSPECTS OF THE DEVELOPMENT OF LEADERSHIP IN GENERAL EDUCATION SCHOOL - Gumuliauskienė, Aušrinė; Vaičiūnienė, Asta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article deals with the problems of the changes and prospects of the development of general education school heads’ and teachers’ leadership: the importance of school heads’ and teachers’ leadership for systemic change of the quality of school activity has been substantiated, the features of the relations between leadership and the changes in school culture and management have been highlighted, the essential tendencies of the expression of teachers’ leadership have been presented; referring to the results of the research school heads’ and teachers’ position about the changes and prospects of the development of leadership in school has been analysed, the essential factors stimulating and impeding the development of leadership in school have been substantiated.